A STUDY OF ROBOTS USED IN EDUCATION - Gheorghe GÎLCĂ; Marian IONESCU (Fiabilitate şi Durabilitate, 2022)
Robots are becoming an integral component of our society and have great potential in being utilized as an educational technology. Our overview shows that robots are primarily used to provide language, science or technology education and that a robot can take on the role of tutor, tool or colleague in the learning activity.